On the equivalence of private and public money - Markus K. Brunnermeier; Dirk Niepelt (Swiss National Bank, Study Center Gerzensee, 2019)
We develop a generic model of money and liquidity that identifies sources of liquidity bubbles and seignorage rents. We provide sufficient conditions under which a swap of monies leaves the equilibrium allocation and price system unchanged. We apply the equivalence result to the "Chicago Plan", cryptocurrencies, the Indian de-monetization experiment, and Central Bank Digital Currency (CBDC). In particular, we show why CBDC need not undermine financial stability.
Keywords: 330; Money creation; monetary system; inside money; outside money; equivalence; CBDC; Chicago Plan; sovereign money; Geldschöpfung; Währungssystem; Münzgewinn; Virtuelle Währung; Amerikanisch; Bargeldloser Zahlungsverkehr; Indisch